The Islamic State in Contemporary Thought: A Critical Analysis of Wael Hallaq’s Perspective - Ahmad , Ibraheem Tayseer (Journal of Posthumanism, 2025)
This study presents a critical analysis of Wael Hallaq’s conception of the Islamic state and the limitations of the modern state. It highlights the fundamental contradictions between the centralized, coercive structure of modern states and the Sharia, which represents a normative order organically rooted in society and attuned to its cultural and religious specificities. Adopting an analytical-critical methodology, the study explores the theoretical foundations of Hallaq’s thesis and situates it within the broader landscape of Islamic political thought. It aims to contribute to academic debates concerning the prospects of political renewal in the Islamic world. The study concludes that a profound incompatibility exists between the modern state and the Sharia—in terms of both organizational philosophy and legislative sovereignty— rendering any attempt at reconciliation highly complex. Furthermore, it uncovers the lasting impact of colonial modernity, particularly in its imposition of legal and cultural hegemony on Muslim societies, which entailed the dismantling of Sharia’s social structures and the replacement of its traditional institutions with Western legal models.